Investigating white matter alterations in Parkinson’s disease using multi-shell free-water DTI and NODDI: insights into neurodegeneration and levodopa effects - Bergamino, Maurizio; Zhu, Shuyi; Shill, Holly A.; Stokes, Ashley M. (Frontiers in Neurology, 2025)
IntroductionParkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms. Levodopa remains the primary treatment, temporarily restoring dopamine levels and improving motor symptoms. Advanced diffusion MRI techniques, such as free-water corrected diffusion tensor imaging (fw-DTI) and neurite orientation dispersion and density imaging (NODDI), provide insights into PD-related microstructural changes beyond conventional DTI.MethodsThis study investigates white matter alterations in PD using multi-shell fw-DTI and NODDI to compare voxel-wise differences between PD patients both OFF and ON levodopa, with comparison to healthy controls (HC). Effect sizes and receiver operating characteristic (ROC) analyses assessed the discriminative power of imaging metrics.ResultsPD (OFF) exhibited increased free-water, reduced neurite density (NDI), and altered orientation dispersion (ODI) in key motor pathways in comparison to HC, while fw-FA offered robust group discrimination (AUC=0.956). Levodopa (ON state) increased NDI and NODDI-FWF, suggesting acute microstructural plasticity, though this finding contrasted with minimal fw-DTI FW changes. Additionally, voxel-based correlation analyses linked free-water and neurite integrity metrics with disease severity.DiscussionOur findings suggest that fw-DTI and NODDI provide complementary information on PD-related neurodegeneration and the transient effects of levodopa. These results underscore the potential of advanced diffusion MRI techniques as biomarkers for tracking PD progression and treatment response.